The broad autism phenotype - Sasson, Noah J. (Henry Stewart Talks, 2020)
History of the Broad Autism Phenotype (BAP) concept, Contemporary conceptualizations, How and for what purpose we measure the BAP, The BAP in the general population: associations with social cognition, social skill, and types of interests, The prevalence of BAP in parents of children on the spectrum, The association between BAP in parents and clinical symptoms in their children, Differences between self-report and informant-reports of BAP traits, General conclusions about the BAP